The limitations of the European economic integration - Kovačević Radovan (Međunarodni Problemi)
It is an important result of economic theory that integration might alter the allocation of resources within a country as well as between countries. Moreover, there are theory-based arguments suggesting that border regions might have an advantage in attracting resources due to their specific location in the center of the integration area. In this paper author have highlighted the continued empirical importance of national borders, even within the EU, which exhibits a much higher degree of economic integration than has been achieved at the global level. Perhaps even more surprising is that capital flows show distinctly similar patterns, a bias towards investment in the home market. In fact it would appear that these two phenomena are closely linked. Thus, whilst globalization has had profound effects on economic actors there is little to suggest that the traditional role for governments in OECD countries in providing social welfare and in regulating the domestic market economy are being undermined. If these borders to international commerce are impervious to further policy initiatives, or if their removal would reduce welfare by, for example undermining individual preferences, then the frictionless world foreseen by some where national administrations become largely impotent in affecting domestic economic outcomes is unlikely to occur. Thus, future discussions concerning global governance will take place between sovereign states that retain substantial discretion in economic policy making in an environment of considerable differences in economic and political power. The author have noted, however, that this situation is apparent for the industrialized countries. In developing countries the situation may be very different. The range of policies that is available in OECD countries is not accessible to many developing countries. In addition the social and business networks and the nature of consumer preferences, which have evolved over many years in OECD countries, and which are key elements in differentiating national from international markets, are not developed to the same extent or take forms which may be inconsistent with and undermined by the increasing use of the market mechanism.